An evaluation of changes over time in serum creatine kinase activity and c-reactive protein concentration in dogs undergoing hemilaminectomy or ovariohysterectomy - Leisewitz, Andrew L. (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2008.